Search 82,933 tutors
FIND TUTORS
Ask a question

Answers by Janesha J.

-4(1-t)+7t (answer)

-4(1-t) + 7t Multiply/Factor out -4 into whats in the parenthesis -4(1-t) ---> (-4) x (1)   (-4) x (-t) Multiply (-4) x (1) ---> -4     (-4) x (-t) ---> 4t (negative times a negative is a positive) So now your problem reads -4 +...

Substitute the variables for the given numbers into the equation 3xy+2x x=2 y=3 ---> 3(2)(3) + 2(2) Use PEMDAS to solve. Multiply first 3(2)(3) + 2(2) ---> 18 +4 Then Add. Solve. 18 +4 ---> 22